A decade of conservation agriculture in intensive cereal systems: Transitioning to soil resilience and stable yield trends in a climate crisis - Jat, Hanuman Sahay; Khokhar, Shivani; Prajapat, Kailash; Choudhary, Madhu; Kakraliya, Manish; Gora, Manoj Kumar; Gathala, Mahesh Kumar; Parbodh Chander Sharma; McDonald, Andrew; Ladha, Jagdish K.; Jat, Mangi Lal (Elsevier, 2025)
Climate change jeopardizes the food security gains achieved in India since the Green Revolution, especially by impacting the productivity of the rice-wheat system in the Indo-Gangetic Plain, a region that serves as the ‘breadbasket’ of South Asia. In this study, we characterized the potential of long-term conservation agriculture (CA) based management practices (i.e., no-tillage, residue retention, and diversified rotations) to stabilize and enhance crop yields in Northwest India. The study consisted of six different production scenarios (Sc) namely Sc I: conventional rice-wheat system; Sc II: partial CA-puddled transplanted rice-zero till wheat-zero till mung bean (TPR-ZTWMb); Sc III: CA-based zero-till direct seeded rice-zero till wheat-zero till mung bean (ZTDSR-ZTWMb); Sc IV: CA-based zero till maize-zero till wheat-zero till mung bean (ZTM-ZTWMb); Sc V: Sc III + subsurface drip irrigation (SSDI); and Sc VI: Sc IV + SSDI. Long-term yield analysis indicated that the CA-based maize-wheat-mung bean system with SSDI (Sc VI) produced approximately 12%, 27% and 35% higher rice equivalent yield (REY), wheat yield and overall system yield, respectively, over to Sc I. Our study examines Wricke's ecovalence index (Wi2) and the sustainability yield index (SYI) to gauge long-term yield stability and sustainability. Consistently higher wheat yields with lower Wi2 and higher SYI were recorded in CA-based scenarios (Sc V: Wi2 = 0.82, SYI = 0.81; Sc VI: Wi2 = 0.85 and SYI = 0.82). CA-based scenarios also demonstrated stable REY over time. The soil physical properties were influenced by CA systems and compared to Sc I, bulk density was −5.89% in Sc V, followed by −3.62% in Sc III and −1.73% in Sc VI. Moreover, CA systems, Sc IV, Sc VI, and Sc V exhibited positive responses by +106%, +99 % and +72%, respectively for water infiltration rates. Overall, soil organic carbon was +83% and +69% with Sc VI and Sc V, respectively than in Sc I. By substantially enhancing soil health and crop productivity, as well as boosting resilience, CA emerges as a promising solution for meeting the increasing food demand in Northwest India and beyond.